The obstinate notion that higher education is a meritocracy - Sobuwa, Simpiwe; McKenna, Sioux (Critical Studies in Teaching and Learning, 2023)
Student success is an enormous concern in light of the high drop-out rates in South African universities. There is a wealth of local and international research which provides complex explanations for these statistics, but the common-sense understanding is that those students who have the right attributes and who work hard will do well. While the notion of higher education as a meritocracy is pervasive, it is invalid given the effects of numerous other mechanisms at play in the students’ educational experiences. This article draws from the literature to discuss the problems of the meritocratic explanation in how it fails to sufficiently account for the centrality of agency and the ways in which this intersects with societal structures. We argue that more useful understandings of student success and failure require social theory that acknowledges the complexities underpinning student success or failure.